Remanufacture of Hot Forging Dies By LMD-p Using a Cobalt Based Hard-Facing Alloy - Ryan Devine; Crawford Cullen; Jim Foster; Mykola Kulakov; Conor MacFadden; Stephen Fitzpatrick (BHM Berg- und Hüttenmännische Monatshefte, 2021)

Risk management to prioritise the eradication of new and emerging invasive non-native species - Olaf Booy; Aileen C. Mill; Helen E. Roy; Alice Hiley; Niall Moore; Pete Robertson; Simon Baker; Matt Brazier; Mathilde Bue; Richard Bullock; Steve Campbell; Dominic Eyre; et al. (Biological Invasions, 2017)

Comparison of non-compartmental and mixed effect modelling methods for establishing bioequivalence for the case of two compartment kinetics and censored concentrations - Jim H. Hughes; Richard N. Upton; David J. R. Foster (Journal of Pharmacokinetics and Pharmacodynamics, 2017)

Foliar phase changes are coupled with changes in storage and biochemistry of monoterpenoids in western redcedar (Thuja plicata) - Adam J. Foster; Roni Aloni; Mario Fidanza; Regine Gries; Gerhard Gries; Jim Mattsson (Trees, 2016)

Selection of low-variance expressed Malus x domestica (apple) genes for use as quantitative PCR reference genes (housekeepers) - Judith Bowen; Hilary S. Ireland; Ross Crowhurst; Zhiwei Luo; Amy E. Watson; Toshi Foster; Nigel Gapper; Jim J. Giovanonni; James P. Mattheis; Chris Watkins; David Rudell; Jason W. Johnston; et al. (Tree Genetics & Genomes, 2014)

Priority research questions for the UK food system - John S. I. Ingram; Hugh L. Wright; Lucy Foster; Timothy Aldred; David Barling; Tim G. Benton; Paul M. Berryman; Charles S. Bestwick; Alice Bows-Larkin; Tim F. Brocklehurst; Judith Buttriss; John Casey; et al. (Food Security, 2013)
The rise of food security up international political, societal and academic agendas has led to increasing interest in novel means of improving primary food production and reducing waste. There are however, also many ‘post-farm gate’ activities that are critical to food security, including processing, packaging, distributing, retailing, cooking and consuming. These activities all affect a range of important food security elements, notably availability, affordability and other aspects of access, nutrition and safety. Addressing the challenge of universal food security, in the context of a number of other policy goals (e.g. social, economic and environmental sustainability), is of keen interest to a range of UK stakeholders but requires an up-to-date evidence base and continuous innovation. An exercise was therefore conducted, under the auspices of the UK Global Food Security Programme, to identify priority research questions with a focus on the UK food system (though the outcomes may be broadly applicable to other developed nations). Emphasis was placed on incorporating a wide range of perspectives (‘world views’) from different stakeholder groups: policy, private sector, non-governmental organisations, advocacy groups and academia. A total of 456 individuals submitted 820 questions from which 100 were selected by a process of online voting and a three-stage workshop voting exercise. These 100 final questions were sorted into 10 themes and the ‘top’ question for each theme identified by a further voting exercise. This step also allowed four different stakeholder groups to select the top 7–8 questions from their perspectives. Results of these voting exercises are presented. It is clear from the wide range of questions prioritised in this exercise that the different stakeholder groups identified specific research needs on a range of post-farm gate activities and food security outcomes. Evidence needs related to food affordability, nutrition and food safety (all key elements of food security) featured highly in the exercise. While there were some questions relating to climate impacts on production, other important topics for food security (e.g. trade, transport, preference and cultural needs) were not viewed as strongly by the participants.

Neglected native or undesirable alien? Resolution of a conservation dilemma concerning the pool frog Rana lessonae - Trevor J. C. Beebee; John Buckley; Ivor Evans; Jim P. Foster; Antony H. Gent; Chris P. Gleed-Owen; Geoffrey Kelly; Graham Rowe; Charles Snell; Julia T. Wycherley; Inga Zeisset (Biodiversity and Conservation, 2005)